Environmental engineering - Peavy, Howard S.; Rowe, Donald R.; Tchobanoglous, George (New York : McGraw-Hill, 1985)
Brings together and integrates the three principal areas of environmental engineering - water, air, and solid waste management. This title introduces an approach by emphasizing the relationship between the principles observed in natural purification processes and those employed in engineered systems. It offers illustrations and problems.
1 Introduction 2 Water Quality; Definitions, Characteristics, and Perspectives 3 Water Purification 4 Engineered Systems for Wastewater Treatment and Disposal 5 Environmental Engineering Hydraulics Design 6 Air Quality Definitions, Characteristics, and Perspectives 7 Engineered Systems for Air Pollution 8 Solid Waste Definitions, Characteristics, and Perspectives 9 Engineered Systems for Solid Waste Management 10 Engineered Systems for Resource and Energy Recovery
Includes bibliographical references and indexes.
Keywords: Environmental engineering